The Effects of graded crude protein diet on serum biochemical parameters of African giant rat (cricetomys gambianus) reared in Ibadan, Nigeria.: Influence of graded crude protein diet on serum biochemical profile of African giant rats. (African Journal of Biomedical Research, 2021)
The domestication of African giant rats  (AGRs)to supplement animal protein needs in Nigeria and its potential as a loboratory animal model for biomedical research have not been fully exploited.30AGRs divided into 5 groups (A-E) were used for this experiment. the rats were smapled on day 28 and day 56 with 2mls of blood obtained from the orbital sinus of the AGRs into lithium heparinized (20u/ml) tubes for serum biochemical analysis. Biochemical standard procedures were employed in analyzing various biochemical constituents. On day 28, significant differences were observed in the levels of sodium, potassium, urea and creatinine at 23.93% CP with 142.75±0.41, 4.35±0.11, 48.00±4.49 and 0.98±0.07 respectively.  The serum protein level revealed significant differences in the levels of albumin and globulin at 27.84% CP with 4.34±0.13 and 2.76±0.11 respectively. Serum liver enzymes indicate significant differences in the levels of ALT at 9.83%CP with 9.50±0.61. Significant increase was also observed in the level of Triglycerides (74.80±4.21) at 27.84% CP. On day 56 there was significant increase in the level of urea (47.00±2.52) at 14.79%CP. Albumin /globulin ratio was significantly higher with 1.60±0.29 at 9.83%CP. There was a significant increase in the level of alkaline phosphatase (ALP) with 40.00±1.53 at 9.83%CP. In conclusion, to the best of our knowledge, the data from this study provide complete biochemical reference data that would be useful in clinical evaluation and management of AGRs. These will be useful in acheiving an appropriate diseases management and domestication plan for this specie of animal.